2012
DOI: 10.1371/journal.pone.0051339
|View full text |Cite
|
Sign up to set email alerts
|

Th22 Cells as Well as Th17 Cells Expand Differentially in Patients with Early-Stage and Late-Stage Myelodysplastic Syndrome

Abstract: BackgroundImmunological mechanisms are increasingly recognized in the progression of myelodysplastic syndrome (MDS). Early-stage MDS (E-MDS) is characterized by autoimmune-mediated myelosuppression whereas late-stage MDS (L-MDS) involves immune evasion, giving dysplastic cells growth potential to progress into acute myeloid leukemia. T-helper (Th) 22 is involved in the pathogenesis of inflammatory autoimmunity and tumorigenesis. The roles of Th22 cells in the pathophysiology of E-MDS and L-MDS remain unsettled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 41 publications
2
39
1
1
Order By: Relevance
“…Another researches in gastric cancer, uterine cervical cancer patients [27, 33] also found significantly elevated frequencies of Th17 cells in peripheral blood as well as in tumor draining lymph nodes. In blood malignant disease, our research showed that Th17 frequencies were increased in early-stage myelodysplastic syndrome (MDS) compared with the late-stage MDS or controls [34]. About the specific role of Th17 cells in peripheral blood of AML patients, the results were controversial, and so far no research was investigated in BM microenvironment of AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another researches in gastric cancer, uterine cervical cancer patients [27, 33] also found significantly elevated frequencies of Th17 cells in peripheral blood as well as in tumor draining lymph nodes. In blood malignant disease, our research showed that Th17 frequencies were increased in early-stage myelodysplastic syndrome (MDS) compared with the late-stage MDS or controls [34]. About the specific role of Th17 cells in peripheral blood of AML patients, the results were controversial, and so far no research was investigated in BM microenvironment of AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…These cells may be involved in epidermal immunity and remodeling in inflammatory skin diseases such as psoriasis, microbial infections, inflammatory and autoimmune diseases (Akdis et al, 2012; Eyerich et al, 2009; Kagami et al, 2010; Muhl et al, 2011; Qiao et al, 2011; Ryan-Payseur et al, 2011; Sanos and Diefenbach, 2013; Shao et al, 2012; Tian et al, 2013; Wolff et al, 2012; Zhang et al, 2011a). …”
Section: 2 T Helper Subsetsmentioning
confidence: 99%
“…The discovery of Th17 and Th22 cells has opened up a new avenue for research into the etiology and treatment of a broad spectrum of diseases. Emerging evidence suggests that the imbalance of Th subsets contributes to the development of immune-related diseases, such as myelodysplastic syndrome (MDS) [9], ankylosing spondylitis (AS) and rheumatoid arthritis (RA) [10]. We and others have previously demonstrated that Th1, Th17 and Th22 cells were elevated, while the frequencies and/or function of Treg cells were suppressed in the peripheral blood of ITP patients[7, 8, 11], indicating a vital role of Th imbalance in the pathogenesis of ITP.…”
Section: Introductionmentioning
confidence: 99%